As docências e os modos de ser docente dos professores de Educação Física no IFRS: experiências de formação, coformação e (de)formação - Locatelli, Tiago (Universidade do Vale do Rio dos Sinos, 2025)
This thesis presents an investigation into the teaching and ways of being a teacher of Physical Education teachers at the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS), who work in technical courses integrated with secondary education. The research sought to answer the following research question: how do Physical Education teachers in technical courses integrated into the IFRS High School develop their teaching and what are their ways of being a teacher at this level of education? Faced with this question, this thesis, linked to the area of Education and Physical Education, aims to understand and analyze the teaching and ways of being a teacher of Physical Education teachers, in a (de)formation research carried out in the Physical Education Teaching Laboratory (LABDOC) of the IFRS. The research materials analyzed were: an online questionnaire — answered by IFRS Physical Education teachers — and the transcripts of the narratives of four LABDOC meetings. The analyses were organized by creating meaning groups that bring together the main recurrences and do not exclude the differences and singularities of the research material. The materials were analyzed using concepts/tools such as: training as (de)training, co-training, craftsmanship, experience, experiments, thought exercises and radical or hyper-critical criticism, which revealed the following results: IFRS Physical Education teaching was understood as plural — teaching — because it is complex, diverse and has different meanings. For this reason, it was characterized as authorial, embodied, committed and engaged. The ways of being a teacher, represented by the ways of being and acting of IFRS Physical Education teachers, were mobilized by legal and institutional recommendations; by different understandings of Physical Education; by different subjectivities; by the specific contexts and structural conditions of each IFRS campus. In view of this, the thesis is defended that the continuing education of Physical Education teachers, even for teachers with postgraduate qualifications, does not guarantee the constitution of a formative ethos. In view of this, there is a need to promote continuing education in the educational institutions where they work, in co-training, in an experimental and experiential way, in order to problematize their teaching and their ways of being a teacher, mobilized by the concept of (de)formation.

Esta tesis presenta una investigación sobre la docencia y los modos de ser docente de los profesores de Educación Física del Instituto Federal de Educación, Ciencia y Tecnología del Río Grande del Sur (IFRS), que actúan en cursos técnicos integrados a la enseñanza media. La pesquisa ha buscado responder a la siguiente cuestión investigativa: ¿cómo los docentes de Educación Física de los cursos técnicos integrados de la enseñanza media de IFRS desarrollan sus docencias y cuáles son sus modos de ser profesores en este nível de enseñanza? Delante de este cuestionamiento, esta tesis, vinculada al área de la Educación y de la Educación Física, visa conocer y analizar las docencias y los modos de ser docente de los profesores de Educación Física, en una pesquisa (de)formación realizada en el Laboratorio de Docencias (LABDOC) de Educación Física del IFRS. Los materiales de pesquisa analizados fueron: un cuestionario enlínea — respondido por los profesores de Educación Física del IFRS — y las transcripciones de las narrativas de cuatro encuentros del LABDOC. Los análisis fueron organizados por medio de la creación de grupos de sentido que reúnen las principales recurrencias y no excluyen las diferencias y las singularidades del material de pesquisa. Por medio de conceptos/herramientas como: formación como (de)formación, coformación, artesanía, experiencia, experimentos, ejercicio de pensamiento y crítica radical o hipercrítica, se realizaron los análisis de los materiales, que evidenciaron los siguientes resultados: la docencia en Educación Física del IFRS fue entendida como plural — docencias — por ser compleja, diversa y con distintos sentidos. Por eso, fue caracterizada como autoral, encarnada y comprometida. Ya los modos de ser docente, representados por los modos de ser y actuar de los profesores de Educación Física del IFRS, fueron movilizados por las recomendaciones legales e institucionales; por los distintos entendimientos acerca de la Educação Física; por las subjetividades diferenciadas; por los contextos específicos y por las condiciones estructurales de cada campi del IFRS. Delante de eso, se defiende la tesis de que la formación continuada de profesores de Educación Física, mismo para los docentes con calificación en nivel de postgrado stricto sensu, no garantiza la constitución de un ethos formativo. Delante de eso, se percibe la necesidad de promover la formación continuada en las instituciones de enseñanza que actúan, en coformación, de manera experimental y experiencial, para problematizar sus docencias y sus modos de ser profesor, movilizados por el concepto de (de)formación.
Keywords: Docência; Educação Física; IFRS; LABDOC; Modos de ser professor; Teaching; Physical Education; Ways of being a teacher; Docencia; Educación Física; Modos de ser profesor; ACCNPQ::Ciências Humanas::Educação